Magnetic properties of acicular ultrafine iron particles - Varanda, Laudemir Carlos [UNESP]; Goya, Gerardo Fabian; Morales, M. Puerto; Marques, Rodrigo Fernando Costa; Godoi, Ricardo Henrique Moreton; Jafelicci Jr., Miguel [UNESP]; Serna, Carlos J. (My University, 2002)
The magnetic properties of acicular ultrafine iron particles are studied. The introduction of high recording densities on recording media has meant a dramatic bit size reduction and track density increase on the media surface. Transmission electron spectroscopy (TEM), x-ray diffraction (XRD), magnetization and Mossbauer spectroscopy (MS) techniques are used to characterize the resulting samples. Results showed that the values of saturation, coercivity and squareness are in agreement with the expected ones for crystalline acicular α-Fe particles.